Near-optimal control of a stochastic SICA model with imprecise parameters - Zine, Houssine (2022)
An adequate near-optimal control problem for a stochastic SICA (Susceptible-Infected-Chronic-AIDS) compartmental epidemic model for HIV transmission with imprecise parameters is formulated and investigated. We prove some estimates for the state and co-state variables of the stochastic system. The established inequalities are then used to prove a necessary and a sufficient condition for near-optimal control with imprecise parameters. The proofs involve several mathematical and stochastic tools, including the Burkholder-Davis-Gundy inequality.